2016
DOI: 10.17676/hae.2016.30.23
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of onset and cessation of rainfall in southwest nigeria: food security impact of of variability in the length of growing season

Abstract: The analysis of onset and cessation of rainfall for selected locations in South west Nigeria was carried out using daily meteorological data for five synoptic stations (Ikeja, Abeokuta, Ondo, Ibadan and Osogbo) in the region. The FAO Rainfall-Evapotranspiration model was used to elucidate the length of growing season and the impact of climate change on climatic variables and agricultural productivity. Results revealed that the wet season lasts from March to November within the period (2001)(2002)(2003)(2004)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…This is similar to studies conducted in West Africa by Laux et al. (2009) ; Odenkunle (2004) ; Sobowale et al. (2016) .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This is similar to studies conducted in West Africa by Laux et al. (2009) ; Odenkunle (2004) ; Sobowale et al. (2016) .…”
Section: Resultssupporting
confidence: 92%
“…And, the farmers reported shift in the onset and that it was becoming unpredictable, highlighting the occurrence dry spell after planting. This is similar to studies conducted in West Africa by Laux et al (2009); Odenkunle (2004); Sobowale et al (2016). Rainfall variability has a direct impact on crop productivity.…”
Section: Areas At Risk Of a Dry Spell At The Beginning Of The Growing Seasonsupporting
confidence: 91%
“…The SWN is geographically located between longitude 8°E and latitude 10°N with a total land area of about 77,818 km 2 and comprise of six states namely Ekiti, Lagos, Ogun, Osun, Oyo and Ondo (Ajayeoba, Atanda, Obadina, Bankole, & Adelowo, 2016;Faleyimu, Agbeja, & Akinyemi, 2010;Sobowale, Sajo, & Ayodele, 2016). The annual rainfall (ca.…”
Section: Study Areamentioning
confidence: 99%
“…For instance, the negative trend recorded in the months of December and February, which are part of dry season in the study area, revealed that dry season farming can only thrive if only water supply for plants can be augmented from other sources. Even though, the results showed that more water was received in November which marks the commencement of dry season in the study area, and also more rain in January, the intense heat often characterized the period has the tendency to aggravate evapotranspiration which could hinder water availability for good plant growth in the period, thus, the need for water supply augmentation earlier mentioned (Atedhor, 2016;Sobowale et al, 2016;Eruola, et al, 2021). Water supply augmentation may include artificial water supply to enhance plant growth as also supported by Sobowale et al, 2016).…”
Section: -Year Trend Of Rainfall By Months: Figures 3(i-xii)mentioning
confidence: 78%